Utility of DNA barcoding in native Oreochromis species. Issue 2 (20th November 2020) - Mojekwu, Tonna O.; Cunningham, Michael J.; Bills, Roger I.; Pretorius, Petrus C.; Hoareau, Thierry B.
Abstract: The importance of Oreochromis in worldwide aquaculture and regional fisheries motivates the study of their genetic diversity in their native range. In this article, all mitochondrial cytochrome c oxidase subunit I gene (COI) sequences of Oreochromis species are retrieved from Barcode of Life Data system to quantify the available DNA barcoding information from wild individuals collected within the native ranges of the respective species. It is found that 70% of the known species in the genus still lack a COI barcode, and only 15% of the available sequences are from within the respective native ranges. Many of the available sequences have been produced from specimens acquired from aquaculture and introduced, naturalized populations, making the assessment of variation within the original native range challenging. Analyses of the wild‐collected fraction of available sequences indicated the presence of cryptic lineages within Nile tilapia Oreochromis niloticus and O. schwebischi, the occurrence of potential introgressive hybridization between O. niloticus and blue tilapia O. aureus, and potential ancestral polymorphism between Karonga tilapia O. karongae and black tilapia O. placidus . This article also reports a case of misidentification of O. mweruensis as longfin tilapia O. macrochir . These results stress the importance of improving the knowledge of genetic variation within the native ranges of Oreochromis species for better‐informed conservation of these natural resources.